Force Normalization in Paraplegics - Serra-Añó, P.; García-Massó, X.; Pellicer, M.; González, L.-M.; López-Pascual, J.; Giner-Pascual, M.; Toca-Herrera, J. L. (International Journal of Sports Medicine, 2012)
The principal aim of our study was the determination of the effectiveness of a standardized ratio, allometric scaling model and a gamma function model in normalizing the isometric torque data of spinal cord patients and healthy subjects. For this purpose we studied a sample of 21 healthy males and 23 spinal cord injury males. The experiment consisted of the measurement of the force of the upper limb movement executed by all the subjects. We also determined anthropometric variables with dual-energy x-ray absorptiometry. The experimental data were analyzed with 3 force normalization methods. Our results indicate that the most important confounding variable was the fat free mass of the dominant upper limb (r>0.36, p<0.05). With the standardization by body mass and allometric scaling model, the normalized torque was influenced by body size variables. However, the normalized torque by the gamma function model was independent of body size measures. Paraplegics were weaker (p<0.05) in extension movements when the data were normalized by the gamma function model. In summary, this study shows that the gamma function model with fat free mass of the dominant upper limb was more effective than the standardized ratio in removing the influence of body size variables.
Keywords: spinal cord injury; body size; muscle strength; shoulder